Secondary prevention of MI: current approaches to treatment. Issue 4 (18th February 2013) - Shah, Anoop; Fox, Keith
Abstract The cornerstones of secondary prevention of MI are drug therapy, cardiac rehabilitation and lifestyle measures. Our Drug review considers the mode of action and evidence base for the wide range of drugs available, followed by sources of further information.